2021
DOI: 10.3390/su14010093
|View full text |Cite
|
Sign up to set email alerts
|

Irish Organics, Innovation and Farm Collaboration: A Pathway to Farm Viability and Generational Renewal

Abstract: The family farm has been the pillar of rural society for decades, stabilising rural economies and strengthening social and cultural traditions. Nonetheless, family farm numbers across Europe are declining as farmers endeavour to overcome issues of climate change, viability, farm structural change and intergenerational farm succession. Issues around farm viability and a lack of innovative agricultural practices play a key role in succession decisions, preventing older farmers from passing on the farm, and young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The implementation of (retro‐)innovative management methods may also apply to family farmers in the case‐study regions and beyond, as shown by Farrell et al. (2021) or Lähdesmäki and Vesala (2022), using organic farming as an example. However, our fieldwork reveals that family farmers encounter difficulties when deviating from mainstream management.…”
Section: Discussing Resultsmentioning
confidence: 99%
“…The implementation of (retro‐)innovative management methods may also apply to family farmers in the case‐study regions and beyond, as shown by Farrell et al. (2021) or Lähdesmäki and Vesala (2022), using organic farming as an example. However, our fieldwork reveals that family farmers encounter difficulties when deviating from mainstream management.…”
Section: Discussing Resultsmentioning
confidence: 99%
“…Stringer et al ( 2020 ) also looks at farmers involved with "movements" centered on farming practices (e.g., slow food, gastronomic movements, artisanal farming) and reports an increased market share of these types of farming in recent years. An article by Farrell et al ( 2022 ) reflects on the opportunity of the organic movement to encourage the next generation of young farmers to commit to the family farm and consider organic farming as a long-term career goal.…”
Section: The Qualitative Syntheses Resultsmentioning
confidence: 99%
“…Other industries can offer them more attractive prospects (Kondo 2021;Bosselmann 2012). Today, the young generation is much more mobile than their ancestors, so there are more learning opportunities, which means that fewer are willing to return home and farm after finishing their education (Farrell et al 2021). However, motivation is positively affected by the spread of new agricultural technologies (for instance, drones, milking robots, automatic steering tractors, etc.).…”
Section: Barriers To Generational Changementioning
confidence: 99%
“…This is linked to urbanization and internal migration, as today the mobility of people is greater than before. Farrell et al (2021), investigating Irish agriculture, mentioned that young people who leave the farm due to further education have a chance of returning if they receive different subsidies in agriculture to start organic farming. The study developed by Popa and Turek Rahoveanu (2021) while researching Olt County in Romania found that education plays an important role in the decision to abandon, start, or continue farming.…”
Section: Education and Knowledge Transfermentioning
confidence: 99%